Prenatal care for pregnant women during the COVID-19 pandemic in Huancavelica, Peru - Jorge-Chahuayo, Maritza (2024)
Objectives: To determine the characteristics of the prenatal care of pregnant women attended in the Ascension Micro network in the period 2019 and 2020. Material and method: observational, retrospective, cross-sectional; the population 619 pregnant women, secondary data recorded in the obstetric VEA and the CNV were used. The report was downloaded in the Excel spreadsheet, and it was analyzed using descriptive statistics in SPSS. Results: Personal characteristics; the pregnant women in both periods are at the optimum reproductive age, are single and cohabiting, with a secondary education level, Ascension origin and most have SIS. APN features; in both periods the beginning of the ANC was in the 1st trimester, more than half have more than 6 ANC, administration of micronutrients, ultrasounds, incomplete home visits in both periods, the laboratory battery, the immune protection, the FIV, the birth plan was complete in the period before the pandemic and incomplete during the pandemic, the delivery was institutional in both periods in a higher percentage. Conclusions: Prenatal care is important in order to prevent future complications and in times of pandemic, integrated work is affected.